Phosphate and transaminase content of epididymal and ejaculated semen of buffalo bulls - GUPTA, H P; SAHNI, K L; MOHAN, G (The Indian Journal of Animal Reproduction, 2005)
Alkaline phosphatase, glutamic oxalo-acetic transaminase and glutamic pyruvic transaminase were studied in the epididymaland ejaculated semen samples to study their role in the epididymal maturation of buffalo spermatozoa. Alkaline phosphatgase (IU/L) averaged 1151.31±213.42, 5531.73±953.85 and 886.66±42.26 in the caput (N = 60) and ejaculated (N = 36) semen, respectively.Corresponding values (IU/L) for lutamic oxalo-acetic transaminase were 149.88±13.65, 649.27±77.69 and 64.97±7.45. Glutamicpyruvic transaminase averaged (IU/L) 10.88±0.96, 102.10±15.91 and 126.78±5.33. These enzmes were associated with epididymalmaturation of buffalo spermatozoa They also helped in maintaining epididymal quiescence and ensuring better tolerance and qualityof semen in terms of motility and morphology of spermatozoa
Keywords: Enzyme; epididymal semen; buffalo